Dinamika Legitimasi Pemerintahan di Tengah Krisis Kepercayaan Publik: Studi Kasus Perkembangan Hukum Tata Negara Pasca-Pemilu 2024 - Ibnu Affan; Gema Ramadhani; Mhd. Rahmani Dayan (Universitas Medan Area, 2026)
This study aims to analyze the dynamics of government legitimacy amid the public trust crisis toward state institutions in the development of Indonesian constitutional law after the 2024 General Election. This research employs a normative juridical method using statutory, case, and conceptual approaches. Legal materials were collected through library research on legislation, Constitutional Court decisions, and relevant constitutional law literature. The findings reveal that the public trust crisis, triggered by controversies surrounding Constitutional Court decisions, allegations of political power abuse, and the weakening of parliamentary oversight functions, has reduced the effectiveness of the checks and balances mechanism within Indonesia’s constitutional system. The dominance of large political coalitions has weakened control over executive power, while the declining moral legitimacy of judicial institutions has generated public distrust toward law enforcement. This condition has encouraged a shift in public participation from formal channels to digital spaces as non-formal instruments of oversight toward state policies. The study concludes that restoring government legitimacy requires constitutional ethics reform, strengthening the independence of state institutions, and developing transparent and meaningful public participation to maintain democratic stability and legal certainty in Indonesia.